Modified insulating coating agent for iron-nickel magnetic powder, preparation method of modified insulating coating agent, insulating coated iron-nickel magnetic powder and iron-nickel magnetic powder core

The iron-nickel magnetic powder core is insulated by the modified insulating coating agent, which solves the problem of the performance of the iron-nickel magnetic powder core degradation under high-temperature annealing conditions, and achieves the effect of improving magnetic permeability and reducing losses at higher annealing temperatures. .

CN119480317APending Publication Date: 2025-02-18HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411757517.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to avoid the limitations and instability of the annealing temperature in the production process of iron-nickel magnetic powder cores, which leads to the fact that it cannot simultaneously have high insulation resistivity and magnetic permeability and low losses under high temperature annealing conditions.

Method used

The iron-nickel magnetic powder matrix is ​​insulated by using a modified insulating coating agent. The modifier includes whisker-shaped inorganic silicone mixture, high-temperature resistant mixture and dispersant solution. Through the coordinated combination of these components, the iron-nickel magnetic powder is improved. The core is fire-retardant, particle strength and insulation.

Benefits of technology

At higher annealing temperatures, the modified insulating coating agent makes the insulating layer of the iron-nickel magnetic powder core less likely to be destroyed, further eliminating internal stress, optimizing microstructure, improving magnetic permeability and reducing losses, thereby at a wider annealing temperature Optimize the process within range to improve the performance of the magnetic powder core.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005166709310000131
    Figure BDA0005166709310000131
  • Figure BDA0005166709310000141
    Figure BDA0005166709310000141
  • Figure BDA0005166709310000151
    Figure BDA0005166709310000151
Patent Text Reader

Abstract

The invention relates to a modified insulating coating agent for iron-nickel magnetic powder, a preparation method of the modified insulating coating agent, insulating coated iron-nickel magnetic powder and an iron-nickel magnetic powder core. The modified insulating coating agent for the iron-nickel magnetic powder comprises a modifier, thermosetting resin and an organic solvent, the modifier comprises a whisker-shaped inorganic silicon mixture, a high-temperature-resistant mixture and a dispersing agent solution. The modified insulation coating agent is adopted for conducting insulation coating on the iron-nickel magnetic powder base body, the iron-nickel magnetic powder core prepared from the insulation-coated iron-nickel magnetic powder can bear higher temperature in the annealing process, and the problem that an insulation layer of the powder is damaged and decomposed due to the high annealing temperature is avoided; the higher annealing temperature is beneficial to further elimination of internal stress and optimization of a microstructure, so that the magnetic conductivity is improved and the loss is reduced; therefore, the process optimization can be carried out in a wider annealing temperature range, so that the improvement effect of high-temperature annealing on the performance of the iron-nickel magnetic powder core can be fully exerted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic materials, in particular to a modified insulating coating agent for iron-nickel magnetic powder and a preparation method thereof, insulating coated iron-nickel magnetic powder and an iron-nickel magnetic powder core. Background Art

[0002] The rapid development of global digitalization, networking and informatization has promoted the rapid progress of electronic technology. The preparation and research of soft magnetic composite materials are closely related to the update of electronic products, and are further developed along with magnetic theory research and scientific and technological innovation. As one of the core components of inductor devices, soft magnetic composite materials need to have excellent soft magnetic properties such as high magnetic permeability, high magnetic induction intensity, low loss and low coercivity, so as to improve the efficiency of magnetoelectric conversion and adapt to the increase of circuit operating frequency.

[0003] Soft magnetic composite materials, also known as magnetic powder cores, are a type of magnetic functional material made by coating a magnetic matrix with an insulating medium and then preparing it through powder metallurgy or 3D printing. Soft magnetic materials have undergone many iterations, with components ranging from simple to complex, with more and more types and improved performance. They have gradually replaced other soft magnetic materials due to their high saturation magnetic induction intensity, low magnetic loss and suitability for high-frequency applications. They are currently the fastest-growing, most promising and most widely used magnetic materials.

[0004] In the process of in-depth discussion of the preparation process of soft magnetic composite powder core materials, a key link that cannot be ignored is high temperature annealing, that is, heat treatment of the powder core to eliminate internal stress and improve the microstructure, so as to achieve the purpose of improving the overall performance of the material. This process is crucial for optimizing the magnetic properties of the powder core and improving its stability and consistency. Although high temperature annealing can bring many benefits, it also hides risks that cannot be ignored. The most critical is the control of the annealing temperature. Once the temperature is set too high and exceeds the range that the powder core material can withstand, it will affect the insulation layer, which is like a fragile protective film that maintains the electrical performance and safety of the entire material. It is a key structure to ensure electrical isolation between particles and prevent short circuits. If it is damaged, the performance of the powder core will be significantly reduced and cannot be used normally.

[0005] High-temperature annealing is an indispensable part of the preparation of magnetic powder cores, but excessively high temperatures are a severe test for the insulation layer, especially for iron-nickel magnetic powder cores. During the preparation process, due to the limitations and instability of the annealing temperature, it is impossible for them to have both high insulation resistivity and magnetic permeability as well as low loss.

[0006] CN113380505A discloses a low-loss magnetic powder core for integrally molded inductors and a preparation method thereof, which uses three organic coating agents, methylphenyl silicone resin, epoxy-modified silicone resin and bisphenol A epoxy resin, to act together for insulation coating, and then adds an inorganic coating agent to complete the bonding, thereby improving the adhesion, coating uniformity and thermal stability of the insulating layer and reducing the loss of the magnetic powder core. However, the magnetic powder core of the invention uses a relatively high pressing pressure, and requires a relatively high annealing temperature to eliminate internal stress, but the annealing temperature applicable to the insulating layer coated by this method is relatively low, resulting in a relatively low overall magnetic permeability performance.

[0007] CN114597050A discloses a method for preparing a modified nano-oxide / kaolin-coated iron silicon aluminum vanadium magnetic powder core, wherein the iron silicon aluminum vanadium magnetic powder core is compositely insulated and coated with modified nano-oxide and kaolin, and a dense and uniform nano-oxide-kaolin insulation layer is formed on the surface of the magnetic powder. Ultrafine kaolin powder is added to the gaps between the iron silicon aluminum vanadium magnetic powder particles coated with the modified nano-oxide, thereby reducing the gaps between the magnetic powder core particles and increasing the density of the magnetic powder core. In terms of magnetoelectric properties, the magnetic permeability and resistivity of the magnetic powder core are improved, and the applicable temperature for stress relief annealing of the magnetic powder core can be as high as 790°C, and the insulation layer has high heat resistance. However, the loss reduction effect of the magnetic powder core of the invention for high temperature annealing is not ideal, and the loss is still relatively high. Whether it is applicable to iron nickel magnetic powder cores is also not disclosed.

[0008] Therefore, how to provide a modified insulating coating agent that can effectively avoid the limitations and instability of the annealing temperature in the production process of the iron-nickel magnetic powder core, so that the iron-nickel magnetic powder core has high insulation resistivity and magnetic permeability and low loss under high temperature annealing conditions, has become a problem that needs to be solved urgently, so as to meet the needs of the soft magnetic powder core field. Summary of the invention

[0009] In order to solve the above technical problems, the present invention provides a modified insulating coating agent for iron-nickel magnetic powder and a preparation method thereof, insulating coated iron-nickel magnetic powder and iron-nickel magnetic powder core. The present invention uses a modified insulating coating agent to perform insulating coating on the iron-nickel magnetic powder matrix. The iron-nickel magnetic powder core prepared by using the insulating coated iron-nickel magnetic powder can withstand higher temperatures during the annealing process, and the insulating layer of the powder will not be damaged and decomposed due to the high annealing temperature; and a higher annealing temperature helps to further eliminate internal stress, optimize the microstructure, and thus improve the magnetic permeability and reduce the loss; therefore, the present invention can perform process optimization within a wider annealing temperature range, so as to give full play to the improvement effect of high temperature annealing on the performance of the magnetic powder core.

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a modified insulating coating agent for iron-nickel magnetic powder, wherein the modified insulating coating agent for iron-nickel magnetic powder comprises a modifier, a thermosetting resin and an organic solvent;

[0012] The modifier comprises a whisker-shaped inorganic silicon mixture, a high temperature resistant mixture and a dispersant solution.

[0013] In the present invention, the modified insulating coating agent for iron-nickel magnetic powder includes a modifier, a thermosetting resin and an organic solvent, wherein the modifier plays an important role. The modifier includes a whisker-shaped inorganic silicon mixture, a high temperature resistant mixture and a dispersant solution, and the whisker-shaped inorganic silicon mixture and the dispersant solution are coordinated and matched, which helps to enhance the performance coordination stability and dispersibility of the modifier system, and then coordinated and matched with the high temperature resistant mixture, so as to improve the fire retardancy of the iron-nickel magnetic powder core, the particle strength, impact resistance, corrosion resistance and the reduction of the expansion rate of the iron-nickel magnetic powder core, and further improve the hot state withstand voltage so that the iron-nickel magnetic powder core is not easy to be broken down during the annealing process. The whisker-shaped inorganic silicon mixture, the high temperature resistant mixture and the dispersant solution are coordinated and matched, so that the iron-nickel magnetic powder core can withstand higher temperatures during the annealing process, so that the comprehensive performance of the iron-nickel magnetic powder core reaches a new height.

[0014] As a preferred technical solution of the present invention, the thermosetting resin includes any one of epoxy resin, polyester resin or silicone resin, or a combination of at least two of them.

[0015] Preferably, the organic solvent includes any one of anhydrous ethanol, acetone or butanol, or a combination of at least two of them.

[0016] Preferably, in the modified insulating coating agent for iron-nickel magnetic powder, the mass ratio of the modifier, the thermosetting resin and the organic solvent is 1:1:(8-12), for example, 1:1:8, 1:1:9, 1:1:10, 1:1:11 or 1:1:12.

[0017] As a preferred technical solution of the present invention, the whisker-like inorganic silicon mixture includes a whisker-like inorganic silicon ceramic material, a pH regulator, a lubricant and a silane coupling agent.

[0018] In the present invention, the whisker-shaped inorganic silicon ceramic material can enhance the coordinated stability of the overall performance of the modified insulating agent and improve the dispersibility, and can be coordinated and interspersed with other components of the modifier for reinforcement.

[0019] Preferably, the whisker-like inorganic silicon ceramic material includes whisker-like silicon carbide and / or whisker-like silicon nitride.

[0020] Preferably, the length of the whisker-shaped inorganic silicon ceramic material is 15 μm-25 μm, for example, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm.

[0021] Preferably, the pH adjuster comprises ammonia water or urea.

[0022] Preferably, the lubricant includes dimethyl silicone oil or amino silicone oil.

[0023] Preferably, the silane coupling agent includes any one of vinyl silane, alkyl silane or amino silane, or a combination of at least two of them.

[0024] It should be noted that in the present invention, there is no specific requirement or special limitation for the specific silane coupling agent materials among the various types of vinyl silane, alkyl silane and amino silane. As long as they are commonly used by technicians in this field, they are applicable to the present invention, for example, they can be γ-aminopropyltriethoxysilane (KH550), 3-aminopropyltrimethoxysilane (KH540), etc.

[0025] Preferably, in the whisker-like inorganic silicon mixture, by weight, the whisker-like inorganic silicon ceramic material comprises 2 to 4 parts, for example, 2, 2.5, 3, 3.5 or 4 parts, etc., the pH adjuster comprises 1 to 3 parts, for example, 1, 1.5, 2, 2.5 or 3 parts, etc., the lubricant comprises 1 to 2 parts, for example, 1, 1.25, 1.5, 1.75 or 2 parts, etc., and the silane coupling agent comprises 1 to 3 parts, for example, 1, 1.5, 2, 2.5 or 3 parts, etc.

[0026] As a preferred technical solution of the present invention, the high temperature resistant mixture includes nano mica, metal oxide, nano polymer flame retardant and binder.

[0027] In the present invention, nano mica, metal oxide and nano polymer flame retardant are coordinated and matched. Among them, nano mica is an active material with a high specific surface area, so it is easier to combine with other materials, and it itself has the characteristics of thermal stability and high temperature resistance, and can maintain good insulation and corrosion resistance under high temperature conditions; the nano polymer flame retardant has a higher glass transition temperature and can remain stable in a high temperature environment, and at the same time has both toughness and rigidity, high strength and fatigue resistance. The three are coordinated and used in combination with a binder, so that the components can be combined more evenly and tightly.

[0028] Preferably, the average particle size D50 of the metal oxide is 5 μm-15 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.

[0029] Preferably, the metal oxide comprises aluminum oxide and / or magnesium oxide.

[0030] In the present invention, metal oxides with a high melting point are more suitable for preparing composite high-temperature thermal insulation materials in combination with inorganic ceramics and other materials, so that the composite high-temperature thermal insulation materials have high strength, hardness, wear resistance, good insulation and thermal conductivity.

[0031] Preferably, the nano polymer flame retardant includes any one of nano polyetheretherketone, nano polyphenylene sulfide, nano polyimide, nano polyetherimide, nano polyamide or nano polyetherketone, or a combination of at least two thereof.

[0032] Preferably, the binder comprises bisphenol A epoxy resin or hydrogenated bisphenol A epoxy resin.

[0033] It should be noted that the bisphenol A epoxy resin used in the present invention is of type E51, and the hydrogenated bisphenol A epoxy resin is of type SH-3000, both of which are low molecular weight epoxy resin materials and are liquid at room temperature.

[0034] Preferably, in the high temperature resistant mixture, by weight, the nano mica comprises 2 to 4 parts, for example, 2, 2.5, 3, 3.5 or 4 parts, etc., the metal oxide comprises 1 to 2 parts, for example, 1, 1.25, 1.5, 1.75 or 2 parts, etc., the nano polymer flame retardant comprises 1 to 2 parts, for example, 1, 1.25, 1.5, 1.75 or 2 parts, etc., and the binder comprises 2 to 4 parts, for example, 2, 2.5, 3, 3.5 or 4 parts, etc.

[0035] Preferably, the dispersant solution comprises kaolin and a solution containing an anionic surfactant.

[0036] In the present invention, kaolin can improve the insulation and compaction density of magnetic powder, and can further improve the homogeneity, hot pressure resistance and firmness of the insulating coating. The dispersant solution and the whisker-like inorganic silicon mixture are coordinated and interlaced for reinforcement, which helps to enhance the performance coordination stability and dispersibility of the modifier system, improve the fire retardancy of the iron-nickel magnetic powder core, the particle strength of the iron-nickel magnetic powder and reduce the expansion rate.

[0037] Preferably, the average particle size D50 of the kaolin is 1 μm-10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0038] Preferably, in the anionic surfactant solution, the anionic surfactant comprises sodium dodecylbenzene sulfonate or sodium dodecyl sulfate.

[0039] Preferably, the mass concentration of the anionic active agent-containing solution is 5wt%-8wt%, such as 5wt%, 6wt%, 7wt% or 8wt%.

[0040] Preferably, in the dispersant solution, by weight, the kaolin comprises 6 to 10 parts, for example 6, 7, 8, 9 or 10 parts, and the anion active agent-containing solution comprises 15 to 25 parts, for example 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 or 25 parts.

[0041] In a second aspect, the present invention further provides a method for preparing the modified insulating coating agent for iron-nickel magnetic powder according to the first aspect, the preparation method comprising the following steps:

[0042] The whisker-shaped inorganic silicon mixture, the high temperature resistant mixture and the dispersant solution are first mixed, and after solid-liquid separation, a modifier is obtained. The modifier, the thermosetting resin and the organic solvent are second mixed to obtain a modified insulating coating agent for iron-nickel magnetic powder.

[0043] As a preferred technical solution of the present invention, the preparation method of the whisker-like inorganic silicon mixture includes: adding a silane coupling agent to a solvent and mixing evenly to obtain a silane coupling agent dispersion, and then evenly mixing the silane coupling agent dispersion, a whisker-like inorganic silicon ceramic material, a pH adjuster and a lubricant to obtain the whisker-like inorganic silicon mixture.

[0044] Preferably, the solvent includes any one of anhydrous ethanol, methanol, ethylene glycol or acetone, or a combination of at least two thereof.

[0045] Preferably, in the silane coupling agent dispersion, by weight, the silane coupling agent comprises 1 to 3 parts, such as 1, 2, or 3 parts, and the solvent comprises 5 to 8 parts, such as 5, 6, 7 or 8 parts.

[0046] Preferably, in the process of obtaining the whisker-shaped inorganic silicon mixture, the mixing method includes ultrasonic dispersion.

[0047] Preferably, in the process of obtaining the whisker-shaped inorganic silicon mixture, the mixing time is 5 min-40 min, for example, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min or 40 min.

[0048] Preferably, before obtaining the whisker-shaped inorganic silicon mixture, the mixed powder is further washed, purified, dried and sieved.

[0049] Preferably, the washing solvent comprises anhydrous ethanol.

[0050] Preferably, the mesh size of the sieve used for the sieving is 600-800 mesh, such as 600 mesh, 650 mesh, 700 mesh, 750 mesh or 800 mesh.

[0051] As a preferred technical solution of the present invention, the preparation method of the high temperature resistant mixture comprises: uniformly mixing nano mica, metal oxide, nano polymer flame retardant and binder, and drying to obtain the high temperature resistant mixture.

[0052] It should be noted that the present invention does not make any specific requirements or special limitations on the mixing method in the process of obtaining the high temperature resistant mixture. As long as it is a method commonly used by technicians in this field, it is applicable to the present invention, for example, it can be mechanical mixing or manual grinding.

[0053] Preferably, the drying method includes baking.

[0054] Preferably, the baking temperature is 270°C-330°C, for example, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C or 330°C.

[0055] In the present invention, the baking temperature is adjusted to 270° C.-330° C., which can promote tighter bonding between the interior of the high-temperature resistant mixture and more uniform crushing.

[0056] Preferably, the baking time is 1 h-2 h, such as 1 h, 1.5 h or 2 h.

[0057] Preferably, after the drying, the dried powder is further cooled, crushed and sieved.

[0058] Preferably, the mesh size of the sieve used for the sieving is 400-600 mesh, such as 400 mesh, 450 mesh, 500 mesh, 550 mesh or 600 mesh.

[0059] Preferably, the method for preparing the dispersant solution comprises: uniformly mixing kaolin and a solution containing an anionic surfactant to obtain the dispersant solution.

[0060] Preferably, in the process of obtaining the dispersant solution, the mixing method includes ultrasonic dispersion.

[0061] Preferably, in the process of obtaining the dispersant solution, the mixing time is 5 min-20 min, for example, 5 min, 10 min, 15 min or 20 min.

[0062] Preferably, the first mixing method comprises ball milling.

[0063] In the present invention, the various components of the modifier can be effectively and evenly mixed by a ball milling mixing method, thereby reducing the negative impact on the magnetic properties of the composite iron-nickel magnetic powder and improving the fluidity of the modifier. When the modified insulating coating agent is mixed with a thermosetting resin for coating, the overall coating effect is more uniform, the coating layer is more solid, and is not easy to be punctured, thereby improving the insulation and heat resistance of the iron-nickel magnetic powder core.

[0064] Preferably, the rotation speed of the ball mill is 1000 r / min-2000 r / min, for example, 1000 r / min, 1200 r / min, 1500 r / min, 1800 r / min or 2000 r / min.

[0065] Preferably, the ball milling time is 1 h-3 h, such as 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0066] Preferably, the solid-liquid separation method includes suction filtration.

[0067] Preferably, after the solid-liquid separation, a drying step is also included.

[0068] Preferably, the second mixing method includes ultrasonic dispersion.

[0069] Preferably, the second mixing time is 5 min-20 min, such as 5 min, 10 min, 15 min or 20 min.

[0070] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0071] The silane coupling agent is added to the solvent and ultrasonically dispersed for 5 minutes to 40 minutes, and mixed to obtain a silane coupling agent dispersion, wherein the silane coupling agent dispersion contains 1 part to 3 parts of the silane coupling agent and 5 parts to 8 parts of the solvent in parts by weight, and then the silane coupling agent dispersion, the whisker-like inorganic silicon ceramic material, the pH regulator and the lubricant are ultrasonically dispersed for 5 minutes to 40 minutes, and mixed, and then the mixed powder is washed, purified, dried and passed through a 600-mesh sieve to obtain a whisker-like inorganic silicon mixture;

[0072] The nano-mica, metal oxide, nano-polymer flame retardant and binder are uniformly mixed, and the mixed powder is then dried by baking at 270° C.-330° C. for 1 h-2 h, and the dried powder is cooled, crushed and sieved through a 400-mesh sieve to obtain a high temperature resistant mixture;

[0073] Ultrasonic dispersion of kaolin and anionic surfactant solution for 5 min to 20 min to obtain a dispersant solution;

[0074] The whisker-like inorganic silicon mixture, the high temperature resistant mixture and the dispersant solution are ball-milled at a rotation speed of 1000r / min-2000r / min for 1h-3h for a first mixing, and after solid-liquid separation, they are dried to obtain a modifier. The modifier, thermosetting resin and organic solvent are ultrasonically dispersed for 5min-20min for a second mixing to obtain a modified insulating coating agent for iron-nickel magnetic powder.

[0075] In a third aspect, the present invention further provides an insulating coated iron-nickel magnetic powder, wherein the insulating coated iron-nickel magnetic powder comprises an iron-nickel magnetic powder matrix and an insulating coating layer coated on the iron-nickel magnetic powder matrix;

[0076] The raw material of the insulating coating layer includes the modified insulating coating agent for iron-nickel magnetic powder as described in the first aspect, or the modified insulating coating agent for iron-nickel magnetic powder prepared by the preparation method described in the second aspect.

[0077] It should be noted that the present invention does not make specific requirements and special limitations on the preparation method of the iron-nickel magnetic powder matrix. As long as it is a preparation method of the iron-nickel magnetic powder matrix commonly used by technical personnel in the field, it is applicable to the present invention, and technical personnel in the field can make adaptive selections and adjustments according to actual conditions.

[0078] Exemplarily, the present invention provides a method for preparing an iron-nickel magnetic powder matrix, the preparation method comprising the following steps:

[0079] 46%-54% iron ingots and 46%-54% nickel ingots are selected and placed in a smelting furnace. After removing impurities, a powder is obtained by a gas atomization method. The powder is sieved to obtain a powder with an average particle size of 10μm-20μm. The powder is annealed in an inert gas annealing furnace at 650℃-850℃ for 4h-6h to obtain the iron-nickel magnetic powder matrix.

[0080] In a fourth aspect, the present invention further provides an iron-nickel magnetic powder core, wherein the raw material of the iron-nickel magnetic powder core comprises the insulating coated iron-nickel magnetic powder as described in the third aspect.

[0081] Compared with the prior art, the present invention has at least the following beneficial effects:

[0082] 1) The present invention adopts a modified insulating coating agent to perform insulation coating on the iron-nickel magnetic powder matrix. The iron-nickel magnetic powder core prepared by the insulating coated iron-nickel magnetic powder can withstand a higher temperature during the annealing process, and the insulation layer of the powder will not be destroyed or decomposed due to the high annealing temperature; and the higher annealing temperature helps to further eliminate internal stress, optimize the microstructure, and thus improve the magnetic permeability and reduce the loss.

[0083] 2) The present invention uses a whisker-shaped inorganic silicon mixture, a high-temperature resistant mixture and a dispersant solution as a modifier, which can improve the particle strength and corrosion resistance of the iron-nickel magnetic powder and reduce the expansion rate. It can also improve the fire retardancy, insulation, thermal conductivity, density and current leakage resistance of the magnetic powder core, improve the hot withstand voltage so that the insulating layer of the iron-nickel magnetic powder core is not easily broken down during annealing, and then the iron-nickel magnetic powder core can withstand higher temperatures during the annealing process, so that the comprehensive performance of the iron-nickel magnetic powder core reaches a new height. DETAILED DESCRIPTION

[0084] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0085] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0086] Example 1

[0087] The present invention provides a modified insulating coating agent for iron-nickel magnetic powder and a preparation method thereof. The modified insulating coating agent for iron-nickel magnetic powder comprises a modifier, a thermosetting resin and an organic solvent in a mass ratio of 1:1:10, and the modifier comprises a whisker-shaped silicon carbide mixture, a high-temperature resistant mixture and a dispersant solution;

[0088] The whisker-like inorganic silicon mixture comprises, by weight, 3 parts of whisker-like silicon carbide (length 20 μm), 2 parts of urea, 1 part of dimethyl silicone oil, and 2 parts of γ-aminopropyltriethoxysilane (KH550);

[0089] The high temperature resistant mixture includes, by weight, 3 parts of nano-mica, 1 part of alumina (average particle size D50 is 10 μm), 1 part of nano-grade polyetheretherketone, and 3 parts of bisphenol A epoxy resin (E51);

[0090] The dispersant solution contains 8 parts of kaolin and 20 parts of anionic active agent solution (mass fraction is 6 wt%) by weight.

[0091] The preparation method comprises the following steps:

[0092] 2 parts of KH550 are added to 7 parts of anhydrous ethanol solvent and ultrasonically dispersed for 10 minutes to obtain a KH550 dispersion, and then 2 parts of urea are added to adjust the pH, and then 3 parts of 20 μm whisker-like silicon carbide and 1 part of dimethyl silicone oil are added and mixed, and ultrasonically dispersed for 30 minutes, and then the mixed powder is washed, purified and dried with anhydrous ethanol, and the dried powder is ground and sieved through an 800-mesh sieve to obtain a whisker-like silicon carbide mixture;

[0093] 3 parts of nano-mica, 1 part of alumina with an average particle size D50 of 10 μm, 1 part of nano-grade polyetheretherketone, and 3 parts of bisphenol A epoxy resin were manually ground and mixed, baked at 330° C. for 1 hour, cooled, crushed, and sieved through a 500-mesh sieve to obtain a high-temperature resistant mixture;

[0094] 8 parts of kaolin with an average particle size D50 of 5 μm are added to 20 parts of a 6 wt % sodium dodecylbenzene sulfonate solution, and mixed and ultrasonically dispersed for 10 minutes to obtain a dispersant solution;

[0095] The whisker-like silicon carbide mixture, the high temperature resistant mixture and the dispersant solution are uniformly mixed, and ball milled at a ball milling speed of 1500 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a modifier;

[0096] The modifier, silicone resin and acetone were mixed in a mass ratio of 1:1:10, and ultrasonically dispersed for 10 minutes to obtain a modified insulating coating agent for iron-nickel magnetic powder.

[0097] The components and contents of the modified insulating coating agent for iron-nickel magnetic powder in Example 2-9 are obtained by changing the parameters on the basis of Example 1, and the specific changed parameters of Example 2-9 are shown in Table 1; the preparation method of the modified insulating coating agent for iron-nickel magnetic powder in Example 2-9 is obtained by changing the parameters on the basis of the steps in Example 1, and the specific changed parameters of Example 2-9 are shown in Table 1.

[0098] The components and contents of the modified insulating coating agent for iron-nickel magnetic powder of Comparative Examples 1-6 are obtained by changing the parameters on the basis of Example 1, and the specific changed parameters of Comparative Examples 1-6 are shown in Table 2; the preparation method of the modified insulating coating agent for iron-nickel magnetic powder of Comparative Examples 1-6 is obtained by changing the parameters on the basis of the steps of Example 1, and the specific changed parameters of Comparative Examples 1-6 are shown in Table 2.

[0099] Application Example 1-9 and Comparative Application Example 1-6

[0100] 50% of iron ingots and 50% of nickel ingots are placed in a smelting furnace, and after removing impurities, a powder is obtained by a gas atomization method, and then sieved to obtain a powder with an average particle size of 15 μm, and annealed in an inert gas annealing furnace at 750° C. for 5 hours to obtain the iron-nickel magnetic powder matrix;

[0101] The iron-nickel magnetic powder provided in Examples 1-9 and Comparative Examples 1-6 is mixed and coated with the modified insulating coating agent and the above-mentioned iron-nickel iron-nickel magnetic powder matrix in a mass ratio of 25:3, ultrasonically dispersed for 5 minutes, baked at 80°C for 1 hour, cooled and crushed to obtain insulating coated iron-nickel magnetic powder; the insulating coated iron-nickel magnetic powder and the demolding powder are fully mixed in a mass ratio of 200:1, and then pressed to obtain a blank, and the above process is repeated to make each example and comparative example have 5 blanks of the same size, and the 5 blanks of the same size in each example and comparative example are respectively placed in a nitrogen atmosphere at 690°C, 720°C, 750°C, 780°C and 810°C for heat treatment for 1 hour to obtain iron-nickel magnetic powder cores at different annealing temperatures, corresponding to Application Examples 1-9 and Comparative Application Examples 1-6, respectively.

[0102] The performance of each iron-nickel magnetic powder core of Example 1-9 and Comparative Application Example 1-6 was evaluated. The inductance value of the initial magnetic permeability μi (1V / 1MHz) of the iron-nickel magnetic powder core was tested using the Chroma 11300 equipment; the IR insulation resistance value of the iron-nickel magnetic powder core was tested using the Chroma 11210 equipment; the loss value of the iron-nickel magnetic powder core was tested using the IWATSU SY-8218 equipment (T=25°C, 1MHz / 50mT). The specific test data are shown in Tables 1 and 2.

[0103] Table 1

[0104]

[0105]

[0106]

[0107]

[0108] Table 2

[0109]

[0110]

[0111]

[0112] Note: “ / ” indicates that the corresponding material is not added

[0113] The test results show that:

[0114] (1) It can be seen from Examples 1-3 in Table 1 that the present invention uses a modified insulating coating agent to insulate the iron-nickel magnetic powder matrix. The iron-nickel magnetic powder core prepared by using the insulating coated iron-nickel magnetic powder can withstand a higher temperature during the annealing process, and a higher annealing temperature helps to further eliminate internal stress, optimize the microstructure, and thereby improve the magnetic permeability and reduce the loss.

[0115] The magnetic permeability of the iron-nickel magnetic powder core of the present invention gradually increases with the increase of annealing temperature, and the loss shows a trend of gradually decreasing with the increase of annealing temperature. Under the annealing condition of 690° C., the core has a higher insulation resistivity, and even with the increase of annealing temperature, the core still has a certain resistivity, which further indicates that the insulating coating layer obtained by the modified insulating coating agent for the iron-nickel magnetic powder of the present invention can significantly improve the performance of the iron-nickel magnetic powder core under high-temperature annealing conditions, so that the overall performance is better.

[0116] (2) It can be seen from Examples 4 and 5 of Table 1 that the present invention can promote tighter bonding between the interior of the high-temperature resistant mixture and more uniform crushing by further adjusting the baking temperature to 270°C-330°C. If the baking temperature is too high, some materials in the high-temperature resistant mixture will melt at high temperature and lose their effectiveness. If the baking temperature is too low, the materials in the high-temperature resistant mixture cannot be well combined and cannot adapt to annealing at high temperature. The loss at high temperature is significantly increased and the insulation resistivity is significantly reduced.

[0117] (3) It can be seen from Examples 6 and 7 in Table 1 that the present invention can prepare a magnetic powder core with strong comprehensive magnetic properties by further limiting the amount of nano-mica to 2-4 parts and the amount of whisker-like silicon carbide to 2-4 parts. If the amount of nano-mica or whisker-like silicon carbide added is too much, the magnetic permeability of the magnetic powder core will be low. Although the insulation resistivity can be improved to a certain extent, the addition of too much non-magnetic material will also increase the overall loss of the material.

[0118] (4) It can be seen from Example 8 in Table 1 that the present invention further limits the mixing of the modifier, thermosetting resin and organic solvent by ball milling. Sufficient ball milling can promote the various components of the modifier to achieve good homogeneity and stability, reduce the negative impact of the modifier components on the overall coating effect, reduce the impact on the magnetic permeability, and make the coating layer more firm and high temperature resistant, improve the insulation and make it difficult for the insulating protective layer to be broken down by high temperature.

[0119] (6) It can be seen from Example 9 in Table 1 that when the present invention uses whisker-like silica, since the whisker-like morphology generally has a higher aspect ratio and excellent corrosion resistance, good mechanical strength and electrical insulation, it can increase the stability, oxidation resistance and thermal shock resistance of the modifier, thereby improving the comprehensive magnetic properties of the magnetic powder core.

[0120] (7) It can be seen from Example 1 and Comparative Examples 1 and 2 in Table 2 that the present invention can effectively improve the insulation resistance value of the iron-nickel magnetic powder core by adding a modifier to the silicone resin as an insulating coating agent for the iron-nickel magnetic powder core, making it suitable for annealing conditions at higher temperatures. The higher annealing temperature helps to further eliminate internal stress, optimize the microstructure, improve magnetic permeability and reduce loss, thereby improving the comprehensive performance of the iron-nickel magnetic powder core.

[0121] However, when there is no modifier, and with the increase of annealing temperature, the loss shows a gradually increasing trend, especially under the annealing condition of 810℃, the loss increases sharply, and under the annealing condition of 690℃, the insulation resistivity is very low. When the annealing temperature increases to 810℃, there is no insulation resistivity at all. Under high temperature annealing conditions, the overall performance is poor.

[0122] (7) It can be seen from Example 1 and Comparative Examples 3-5 in Table 2 that when the whisker-like inorganic silicon mixture is omitted, the high-temperature resistant mixture is omitted, or only the dispersant solution is added to the modifier, the high-temperature resistance of the prepared iron-nickel magnetic powder core is increased, but the high-temperature loss is still high and the magnetic permeability is also decreased.

[0123] (8) It can be seen from Example 1 and Comparative Example 6 in Table 2 that when the whisker-like inorganic silicon mixture is not used, the overall stability of the modifier is reduced, and the components are unevenly dispersed, and the mutual reinforcement effect cannot be reflected, which leads to a decrease in insulation performance. The insulating coating layer is easily broken down when facing a higher annealing temperature, and the loss increases significantly at a high annealing temperature of about 810°C.

[0124] In summary, the present invention provides a modified insulating coating agent for iron-nickel magnetic powder and a preparation method thereof, insulating coated iron-nickel magnetic powder and iron-nickel magnetic powder core. The present invention uses a modified insulating coating agent to perform insulating coating on the iron-nickel magnetic powder matrix, and the iron-nickel magnetic powder core prepared by using the insulating coated iron-nickel magnetic powder can withstand higher temperatures during the annealing process, and the insulating layer of the powder will not be damaged and decomposed due to the high annealing temperature; and a higher annealing temperature helps to further eliminate internal stress, optimize the microstructure, and thus improve the magnetic permeability and reduce the loss; therefore, the present invention can perform process optimization within a wider annealing temperature range, so as to give full play to the improvement effect of high temperature annealing on the performance of the magnetic powder core.

[0125] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A modified insulating coating agent for iron-nickel magnetic powder, characterized in that: The modified insulating coating agent for iron-nickel magnetic powder comprises a modifier, a thermosetting resin and an organic solvent; The modifier comprises a whisker-shaped inorganic silicon mixture, a high temperature resistant mixture and a dispersant solution.

2. The modified insulating coating agent for iron-nickel magnetic powder according to claim 1, characterized in that: The thermosetting resin includes any one of epoxy resin, polyester resin or silicone resin or a combination of at least two thereof; Preferably, the organic solvent comprises any one of anhydrous ethanol, acetone or butanol, or a combination of at least two thereof; Preferably, in the modified insulating coating agent for iron-nickel magnetic powder, the mass ratio of the modifier, the thermosetting resin and the organic solvent is 1:1:(8-12).

3. The modified insulating coating agent for iron-nickel magnetic powder according to claim 1 or 2, characterized in that: The whisker-shaped inorganic silicon mixture comprises a whisker-shaped inorganic silicon ceramic material, a pH regulator, a lubricant and a silane coupling agent; Preferably, the whisker-like inorganic silicon ceramic material comprises whisker-like silicon carbide and / or whisker-like silicon nitride; Preferably, the length of the whisker-shaped inorganic silicon ceramic material is 15 μm-25 μm; Preferably, the pH adjuster comprises ammonia or urea; Preferably, the lubricant comprises dimethyl silicone oil or amino silicone oil; Preferably, the silane coupling agent includes any one or a combination of at least two of vinyl silane, alkyl silane or amino silane; Preferably, in the whisker-like inorganic silicon mixture, in parts by weight, the whisker-like inorganic silicon ceramic material comprises 2 to 4 parts, the pH adjuster comprises 1 to 3 parts, the lubricant comprises 1 to 2 parts, and the silane coupling agent comprises 1 to 3 parts.

4. The modified insulating coating agent for iron-nickel magnetic powder according to any one of claims 1 to 3, characterized in that: The high temperature resistant mixture comprises nano mica, metal oxide, nano polymer flame retardant and binder; Preferably, the average particle size D50 of the metal oxide is 5 μm-15 μm; Preferably, the metal oxide comprises aluminum oxide and / or magnesium oxide; Preferably, the nano polymer flame retardant comprises any one of nano polyether ether ketone, nano polyphenylene sulfide, nano polyimide, nano polyether imide, nano polyamide or nano polyether ketone, or a combination of at least two thereof; Preferably, the binder comprises bisphenol A epoxy resin or hydrogenated bisphenol A epoxy resin; Preferably, in the high temperature resistant mixture, by weight, the nano mica comprises 2 to 4 parts, the metal oxide comprises 1 to 2 parts, the nano polymer flame retardant comprises 1 to 2 parts, and the binder comprises 2 to 4 parts; Preferably, the dispersant solution comprises kaolin and an anionic surfactant solution; Preferably, the average particle size D50 of the kaolin is 1 μm-10 μm; Preferably, in the anionic surfactant solution, the anionic surfactant comprises sodium dodecylbenzene sulfonate or sodium dodecyl sulfate; Preferably, the mass concentration of the anionic active agent solution is 5wt%-8wt%; Preferably, in the dispersant solution, the kaolin comprises 6 to 10 parts by weight and the anionic surfactant solution comprises 15 to 25 parts by weight.

5. A method for preparing a modified insulating coating agent for iron-nickel magnetic powder according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The whisker-shaped inorganic silicon mixture, the high temperature resistant mixture and the dispersant solution are first mixed, and after solid-liquid separation, a modifier is obtained. The modifier, the thermosetting resin and the organic solvent are second mixed to obtain a modified insulating coating agent for iron-nickel magnetic powder.

6. The preparation method according to claim 5, characterized in that: The preparation method of the whisker-shaped inorganic silicon mixture comprises: adding a silane coupling agent into a solvent and mixing them uniformly to obtain a silane coupling agent dispersion, and then uniformly mixing the silane coupling agent dispersion, a whisker-shaped inorganic silicon ceramic material, a pH regulator and a lubricant to obtain the whisker-shaped inorganic silicon mixture; Preferably, the solvent comprises any one of anhydrous ethanol, methanol, ethylene glycol or acetone, or a combination of at least two thereof; Preferably, in the silane coupling agent dispersion, the silane coupling agent comprises 1 to 3 parts and the solvent comprises 5 to 8 parts by weight.

7. The preparation method according to claim 5 or 6, characterized in that: The preparation method of the high temperature resistant mixture comprises: uniformly mixing nano mica, metal oxide, nano polymer flame retardant and binder, and drying to obtain the high temperature resistant mixture; Preferably, the drying method includes baking; Preferably, the baking temperature is 270°C-330°C; Preferably, the baking time is 1h-2h; Preferably, the method for preparing the dispersant solution comprises: uniformly mixing kaolin and a solution containing an anionic active agent to obtain the dispersant solution; Preferably, the first mixing method comprises ball milling; Preferably, the rotation speed of the ball mill is 1000r / min-2000r / min; Preferably, the ball milling time is 1 h-3 h.

8. The preparation method according to claim 5, characterized in that: The preparation method comprises the following steps: The silane coupling agent is added to the solvent and ultrasonically dispersed for 5 minutes to 40 minutes, and mixed to obtain a silane coupling agent dispersion, wherein the silane coupling agent dispersion contains 1 part to 3 parts of the silane coupling agent and 5 parts to 8 parts of the solvent in parts by weight, and then the silane coupling agent dispersion, the whisker-like inorganic silicon ceramic material, the pH regulator and the lubricant are ultrasonically dispersed for 5 minutes to 40 minutes, and mixed, and then the mixed powder is washed, purified, dried and passed through a 600-mesh sieve to obtain a whisker-like inorganic silicon mixture; The nano-mica, metal oxide, nano-polymer flame retardant and binder are uniformly mixed, and the mixed powder is then dried by baking at 270° C.-330° C. for 1 h-2 h, and the dried powder is cooled, crushed and sieved through a 400-mesh sieve to obtain a high temperature resistant mixture; Ultrasonic dispersion of kaolin and anionic surfactant solution for 5 min to 20 min to obtain a dispersant solution; The whisker-like inorganic silicon mixture, the high temperature resistant mixture and the dispersant solution are ball-milled at a rotation speed of 1000r / min-2000r / min for 1h-3h for a first mixing, and after solid-liquid separation, they are dried to obtain a modifier. The modifier, thermosetting resin and organic solvent are ultrasonically dispersed for 5min-20min for a second mixing to obtain a modified insulating coating agent for iron-nickel magnetic powder.

9. An insulating coated iron-nickel magnetic powder, characterized in that: The insulating coated iron-nickel magnetic powder comprises an iron-nickel magnetic powder matrix and an insulating coating layer coated on the iron-nickel magnetic powder matrix; The raw material of the insulating coating layer includes the modified insulating coating agent for iron-nickel magnetic powder as described in any one of claims 1-4, or the modified insulating coating agent for iron-nickel magnetic powder prepared by the preparation method as described in any one of claims 5-8.

10. An iron-nickel magnetic powder core, characterized in that: The raw material of the iron-nickel magnetic powder core includes the insulating coated iron-nickel magnetic powder as claimed in claim 9.

Citation Information

Patent Citations

  • Low-loss magnetic powder core for integrally-formed inductor and preparation method of low-loss magnetic powder core

    CN113380505A